Use of the House-Tree-Person Projective Drawings and Parental Styles Inventory in the Global Psychological Evaluation of Transgender Youth Who Seek Healthcare at the Gender Identity Program - Soll, Bianca Machado Borba; Brandelli Costa, Angelo; Vaitses Fontanari, Anna Martha; Chinazzo, Ítala Raymundo; da Silva, Dhiordan Cardoso; Schwarz, Karine; Schneider, Maiko Abel; Bridi Filho, Cesar Augusto Nunes; Garcia de Garcia, Claudia; Real, André; Tramontina, Silza; Lobato, Maria Inês Rodrigues (Frontiers in Psychology, 2019)
The present study explores data collected in the psychological evaluation of transgender youth and their families who seek healthcare at the Gender Identity Program. Great psychosocial changes mark the transition from infancy to adulthood. Transgender youth may have these aspects of their developmental stage potentialized. A study was conducted with 23 transgender youth (mean age=14±2.38 years) and their caregivers. Eleven of the youngsters were assigned male at birth, while twelve were assigned female. The research protocol consisted of a survey and systematization of the data collected in the initial global psychological evaluation performed at the healthcare facility, including House-Tree-Person (HTP) projective drawings and the Parental Styles Inventory. The present study aimed to explore the data collected during the psychological evaluation of youngsters diagnosed with gender incongruence, relating the HTP projective drawing technique to parental styles and gender trajectories. The results indicate two key points. One evidenced that parental styles could be either preventive or risk components in maintaining adequate socialization in these young people but not in affecting the level of gender dysphoria. The other was that coherence is introduced in the person's perception of his or her projected self-image and his or her expressed gender as he/she becomes more comfortable in expressing his/her gender identity. Treating youngsters inherently brings ethical issues to clinical practice. Thus, global psychological evaluation tailored to this population is a fundamental resource that the psychology professional can use in consultations with youngsters because this tool brings a global understanding about the natural development cycle, facilitating the formulation of therapeutic conducts and exchanges within interdisciplinary transgender health care teams.